A sensitivity and specificity comparison of fine needle aspiration cytology and core needle biopsy in evaluation of suspicious breast lesions: A systematic review and meta-analysis. (February 2017) - Wang, Mei; He, Xiaoning; Chang, Yaping; Sun, Guangwen; Thabane, Lehana
Abstract: Purpose: Breast cancer detections for women with suspicious lesions mainly depend on two non-operative pathological tests-fine needle aspiration cytology (FNAC) and core needle biopsy (CNB). The aim of this systematic review was to compare the sensitivity and specificity of CNB and FNAC in this setting. Methods: The data sources included MEDLINE, EMBASE, PubMed, and the Cochrane Central Register of Controlled Trials (CENTRAL) till February 2016. We included prospective series of studies which directly compared the accuracy of FNAC and CNB. We used forest plots to display the sensitivity and specificity of FNAC and CNB respectively. Pre-specified subgroup analyses and sensitivity analysis were conducted. Results: Ultimately, 12 articles (1802 patients) were included in the final analysis. The pooled analysis shows that the sensitivity of CNB is better than that of FNAC [87% (95% CI, 84%–88%, I 2  = 88.5%) versus 74% (95% CI, 72%–77%, I 2  = 88.3%)] and the specificity of CNB is similar to that of FNAC [98% (95% CI, 96%–99%, I 2  = 76.2%) versus 96% (95% CI, 94%–98%, I 2  = 39.0%)]. For subgroup analysis, the sensitivities of both tests are better for palpable lesions than that of non-palpable lesions. Sensitivity analysis shows the robustness of the primary analysis. Conclusion: Our study suggests that both of FNAC and CNB have good clinical performance. In similar circumstances, the sensitivity of CNB is better than that of FNAC, while their specificities are similar. FNAC could be still considered the first choice to evaluate suspicious nonpalpable breast lesions. Highlights: The sensitivity of CNB is better than that of FNAC [87% (95% CI 84% to 88%) versus 74% (95% CI 72% to 77%)]. The specificity of CNB is similar to that of FNAC [98% (95% CI 96% to 99%) vs. 96% (95% CI 94% to 98%)]. The specificity of FNAC is better for non-palpable lesions (under guidance) than palpable lesions from subgroup analysis. Under the adjuvant guidance, FNAC could be still considered the first choice to evaluate non-palpable lesions.